Analisis kesulitan menyelesaikan soal cerita materi fpb dan kpk kelas iv sekolah dasar ditinjau dari gaya kognitif - Nur Insani; Riyadi Riyadi; Siti Kamsiyati (Universitas Sebelas Maret, 2022)
This study aims to determine the difficulties in solving the story problem material of HCF and LCM in students of class IV MI Syafaat Muhammadiyah with a cognitive style field dependent and field independent. The research method used is qualitative with a case study approach. subjects were selected by purposive sampling, obtained 6 research subjects based on the results of the GEFT test. Data collection techniques in this study used the test, interview, and documentation methods. The analytical framework was developed based on Newman’s error category. The results of the analysis obtained five error types, namely (1) reading errors, (2) comprehension errors, (3) transformation errors, (4) process skills errors, (5) encoding errors. From the results of the analysis, it was found that the difficulty of students in solving story problems was (a) lack of comprehension of the problem posed, (b inability to translate the problem into mathematical form), (c) lack of strategy knowledge, (d) inability to use the correct mathematics. The difficulties that most often occur to students are difficulties in applying the HCF and LCM concepts and difficulties in carrying out mathematical arithmetic operations.